PENINGKATAN KESEJAHTERAAN KELUARGA MELALUI PENGEMBANGAN USAHA BATU BATA DI KELURAHAN SUKODADI PALEMBANG - Selly Hardianti Nadelia (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2023)
This article aims to examine research related to the assistance and obstacles experienced by brick makers during the work process and to determine the level of welfare of brick maker business families. The method used in this study is a descriptive qualitative method through field research using data collection in the form of observation, interviews and documentation. The author can conclude that the brick business activities do not have work assistance for their employees both from the beginning of work to pursue the job, this is because the people who choose to work as brick makers only rely on experience and self-taught lessons. Then related to the obstacles that are often encountered by employees is the weather that is not supportive during the drying process of bricks that have been molded. Regarding the level of family welfare, there are employees who are classified as families below the Prosperous III Plus level because one of them is that the condition of the house occupied does not have a good roof, floor and wall completeness.